Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/1757743815586520
|View full text |Cite
|
Sign up to set email alerts
|

“Zebra world”: The promotion of imperial stereotypes in a children’s book

Abstract: Learning materials have become significant determinants of quality learning environments for young children. This study presents an example of such learning material in the Finnish context -a children's book entitled: Bibi muuttaa Suomeen (translated: Bibi Moves to Finland) by Katja Kallio and Maggie Lindholm (2005). The main concern of this article is how the 'us' and 'them' (Finland vs. Africa) meet or co-exist together in the book, which describes a young girl, Bibi, her life in a 'traditional' African vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Since then, several studies have reported that males are often portrayed as active and dominating, while females are instead described as passive and soft [50,65,72]. Other studies have found the presence of racial bias [53], stereotypes against disability [6], and occupation [36] in children's books. Researchers have argued that the presence of such stereotypes in children's books is severely problematic as children are susceptible to inheriting stereotypes at an early age [50,91].…”
Section: Bias In Creative Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several studies have reported that males are often portrayed as active and dominating, while females are instead described as passive and soft [50,65,72]. Other studies have found the presence of racial bias [53], stereotypes against disability [6], and occupation [36] in children's books. Researchers have argued that the presence of such stereotypes in children's books is severely problematic as children are susceptible to inheriting stereotypes at an early age [50,91].…”
Section: Bias In Creative Writingmentioning
confidence: 99%
“…Thus, it is imperative for written stories to not promote biased representation of minority and marginalized groups. However, current literature is filled with tired, unoriginal, and sometimes harmful stereotypes related to race, gender, sexuality, ethnicity, and age, such as the trope of the angry African-American woman, the studious Asian person, or the helpless damsel in distress [6,24,41,45,50,53,67,69].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies exist in the Finnish context that have documented the need for multicultural education and respective teacher training (e.g., Acquah & Commins, 2013), but research that explicitly addressed racism is harder to come by. Although the recent past has seen important attempts to bring antiracism education into the public debate and into schools (Alemanji, 2016; Alemanji & Dervin, 2016; Alemanji & Mafi, 2018; Armila, Rannikko, & Sotkasiira, 2018; Layne & Alemanji, 2015), such studies remain scarce. Similarly, CWS is still in its infancy in Finland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the teachers talked about their teaching experiences and practices, many mentioned the importance of knowing the characteristics of their learners. Several teachers' comments about Finnish learners echoed stereotypes about Finns: They are quiet, shy perfectionists (Layne & Alemanji, 2015). These characteristics were regarded as obstacles for effective, fun intercultural teaching of Chinese.…”
Section: Finnish Students Are Too Shymentioning
confidence: 99%